Assessing Mental Health Status among Primary School Children - LEE, MOI CHING; Jiar, Yeo Kee; Jaffri, Hadijah (Advances in Social Sciences Research Journal, 2015)
Mental health is the way we think or feel about ourselves, what is going on around us, and how we cope with the stresses of life and challenges, and those affects our sense of wellbeing as well as our physical health. Mental health refers to the cognitive and behavioral wellbeing of oneself due to the awareness towards situational and environmental activities as well as coping mechanism that one adopts to overcome stress and life challenges. In general, it is important to have good mental health in order to have better quality of life. Good mental health is important in learning and life, to meet challenges in life. In the present study, the researcher examined the primary children’s mental health status. A total of 123 children from five Chinese-medium National Type Schools in Johor, Malaysia participated in this study. Strengths and Difficulties Questionnaire (SDQ) was used to identify the mental health difficulties of children in Year Two and Year Three. The children’s mental health statuses were evaluated by their class teachers, and 41 teachers involved in the evaluation. Semi-structured interview were conducted after the SDQ. Three teachers were selected to be interviewed. From this study, it was found that many of the children are suspected to have high risk for mental health difficulties. The findings in this study showed that conduct problems are the most significant problems, followed by hyperactivity problems, emotional problems, and peer problems. Generally, the teachers aware the children’s problems, and understood that social-emotional learning is the best way to enhance children’s mental health wellbeing.